Evaluation of Business Cycle Synchronization by the Oil Revenues (Markov Switching Bayesian VAR Analysis) - AmirTeymoori, Raziyeh; Jalaee, Seyed AbdolMajid; ZayandehRoodi, Mohsen (International Journal of Contemporary Economics and Administrative Sciences, 2018)
The synchronization of business cycles is one of the new topics that have been raised in recent decades in the field of international business at the same time of increased economic integration between countries. Accordingly, considering the influenced Iranian economy by the flow of business cycles, and given that synchronization is investigated by the existence of common factors, so in this study, the synchronization of business cycles of a country as OPEC member with the important and influential factors of oil, which have a significant effect on both the economy of the country and the world, has been studied. Due to the formation of business cycles and the process of oil revenue, the method used is Markov Bayesian VAR Switching (MSBVAR) analysis. According to the obtained results, the synchronization of business cycles between Iran and Iraq during 1985-2015 indicates the high synchronization and symmetry between the two countries’ business cycles. The role of oil revenues is significant in justifying the degree of synchronization of business cycles. Regimen 1 (Stagnation) has been more stable than Regime 2 (Inflation) and Regime 1is more likely to be dominant.